2018
DOI: 10.2166/wcc.2018.120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the uncertainties of climate change on the performance of hydropower systems

Abstract: This study's objective is to assess the potential impact of climate change on an example underdesign hydropower system in the Karkheh River basin, Iran. Based on three water resources performance criteria (reliability, resiliency, and vulnerability), a novel framework was proposed to interpret and cope with the uncertainties associated with such assessments. The results demonstrated the acceptable performance of the system in most months, while there were certain signs for rare low-inflows, and consequently lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The IHACRES model is an applied model used throughout the world that recent successful application of this model caused we chose this model (Sriwongsitanon and Taesombat, 2011;Samuel et al, 2011;Onyutha, 2019). One of the major advantages of this model over other hydrological models is the minimal data input requirement (Zolghadr et al, 2018). This model engages either linear, nonlinear, or multiple regression methods to estimate streamflow (Jakeman et al, 1990;Samuel et al, 2011).…”
Section: Description Of the Ihacres Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The IHACRES model is an applied model used throughout the world that recent successful application of this model caused we chose this model (Sriwongsitanon and Taesombat, 2011;Samuel et al, 2011;Onyutha, 2019). One of the major advantages of this model over other hydrological models is the minimal data input requirement (Zolghadr et al, 2018). This model engages either linear, nonlinear, or multiple regression methods to estimate streamflow (Jakeman et al, 1990;Samuel et al, 2011).…”
Section: Description Of the Ihacres Modelmentioning
confidence: 99%
“…This indicates that both these models exhibit high performance in humid (vs. arid) regions, which concurs with the results of many other studies (a summary of these studies is shown in Table Ⅶ). In some of these studies (Zolghadr et al, 2018;Sayasane et al, 2016), it was put forward that model weakness in arid regions compared to humid regions may be the result of rainfall intensity and distribution in arid regions.…”
Section: Comparing the Models Performance According To Climatementioning
confidence: 99%
“…5(c) shows an increase in the vulnerability of the Dez system across most RCPs, indicating that despite the higher reliability and resiliency of the reservoir, the damages of a failure event will be more severe than historical performance. Zolghadr-Asli et al (2019) also indicated that climate change will increase the reliability and resiliency of hydro-power production of the Karkheh reservoir, located in the same region in Iran, while the vulnerability will also increase and produce severe blackouts. Our results also show that considering the historical release policies of the reservoir and ignoring the effects of climate change in defining the operating policies will result in system failure and will produce serious damages.…”
Section: Rrvmentioning
confidence: 99%
“…We chose the IHACRES model because it is applied throughout the world and has been recently applied with success (Samuel et al, 2011;Sriwongsitanon and Taesombat, 2011;Onyutha, 2019). One of the major advantages of this model over other hydrological models is the minimal data input requirement (Zolghadr-Asli et al, 2018). It engages either linear, nonlinear, or multiple regression methods to estimate streamflow (Jakeman et al, 1990;Samuel et al, 2011).…”
Section: Description Of the Ihacres Modelmentioning
confidence: 99%